2020
DOI: 10.1136/rmdopen-2020-001257
|View full text |Cite
|
Sign up to set email alerts
|

Urine and serum S100A8/A9 and S100A12 associate with active lupus nephritis and may predict response to rituximab treatment

Abstract: BackgroundApproximately 30% of patients with the systemic autoimmune/inflammatory disorder systemic lupus erythematosus (SLE) develop lupus nephritis (LN) that affects treatment and prognosis. Easily accessible biomarkers do not exist to reliably predict renal disease. The Maximizing SLE Therapeutic Potential by Application of Novel and Systemic Approaches and the Engineering Consortium aims to identify indicators of treatment responses in SLE. This study tested the applicability of calcium-binding S100 protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 37 publications
2
23
0
Order By: Relevance
“…35 Additionally, a combination of serum S100A8/A9 and S100A12 was shown to predict rituximab treatment response in lupus nephritis. 36 The expression of the proinflammatory proteins S100A9 and S100A12 was found to be significantly increased in monocytes and neutrophils at day five after rituximab treatment. Conversely, S100A8/A9 and S100A12 serum levels significantly decreased and therefore secretion by effector cells is lower at day five after treatment.…”
Section: Discussionmentioning
confidence: 93%
“…35 Additionally, a combination of serum S100A8/A9 and S100A12 was shown to predict rituximab treatment response in lupus nephritis. 36 The expression of the proinflammatory proteins S100A9 and S100A12 was found to be significantly increased in monocytes and neutrophils at day five after rituximab treatment. Conversely, S100A8/A9 and S100A12 serum levels significantly decreased and therefore secretion by effector cells is lower at day five after treatment.…”
Section: Discussionmentioning
confidence: 93%
“…Taken together, our results emphasise the need to identify novel biomarkers that will improve the predictive accuracy for treatment response in patients with SLE over and above the modest performance of clinical factors alone. Urinary biomarkers have recently been demonstrated to predict treatment response to rituximab in LN at 6 months 35. Adding such factors into our models would likely further improve their predictive value.…”
Section: Discussionmentioning
confidence: 98%
“…Davies et al. ( 37 ) found that serum and urine S100A8 levels were elevated in patients with SLE, and the urine/serum ratios were elevated in patients with active LN. Tantivitayakul et al.…”
Section: Discussionmentioning
confidence: 99%